Managing project stakeholders : building a foundation to achieve project goals - Roeder, Tres, 1968- (Wiley, 2013)
The keys to project management success delivered by one of the world's most respected experts in the field Why do some project managers achieve their project goals while others fail? Drawing on his years of experience as a recognized global expert on project management and organizational change, author Tres Roeder answers that question, and lays out a proven path to project success. Focusing on the major differences between project management and other types of management-not least of them being the temporary nature of projects versus the repetitive nature of most manager.